Conducting Educational Needs Assessments - Stufflebeam, D.L. author. aut Link
XV, 229 p.
Keywords: What goals should be addressed by educational programs? What priorities should be assigned to the different goals? What funds should be allocated to each goal? How can quality services be maintained with declining school enrollments and shrinking revenues? What programs could be cut if necessary? The ebb and flow of the student population, the changing needs of our society and the fluctuation of resources constantly impinge on the education system. Educators must deal with students, communities, and social institutions that are dynamic, resulting in changing needs. It is in the context of attempting to be responsive to these changes, and to the many wishes and needs that schools are asked to address, that needs assessment can be useful. Needs assessment is a process that helps one to identify and examine both values and information. It provides direction for making decisions about programs and resources. It can include such relatively objective procedures as the statistical description and analysis of standardized test data and such subjective procedures as public testimony and values clarification activities. Needs assessment can be a part of community relations, facilities planning and consolidation, program development and evaluation, and resource allocation. Needs assessment thus addresses a xiii XIV PREFACE broad array of purposes and requires that many different kinds of procedures be available for gathering and analyzing information. This book was written with this wide variation of practices in mind.